ПАСТКА ДЛЯ ГЕТЬМАНИЧА: СУЧАВСЬКА КАМПАНІЯ Т. ХМЕЛЬНИЦЬКОГО (1653) - Чучко, Михайло Костянтинович; Chuchko, Mykhaylo; Chuchko, Mykhailo (Науковий вісник Чернівецького університету імені Юрія Федьковича: Історія., 2023)
The article deals with the problems of difficult relations between the Moldavian prince Vasile Lupu and the Zaporozhzhia Army after the start of the War of Liberation in Ukraine under the leadership of Hetman B. Khmelnytskyi against Polish domination. The conclusion of a forced alliance, sealed in 1652 by the marriage of Vasile Lupu’s daughter Ruksandra and B. Khmelnytskyi’s son Tymofii, later led to a political crisis within the principality and confrontation with the rulers of neighboring Wallachia and Transylvania in the international arena. Due to the rebellion of the discontented boyars, led by the great logothete Gheorghe Ștefan, who were supported by the prince of Wallachia Matei Basarab and the prince of Transylvania George II Rákóczi, in the spring of 1653 Vasile Lupu briefly lost power, but soon returned the throne with the help of the Cossacks of hetmanych T. Khmelnytskyi. However, the attempt of the prince of Moldavia to use the armed forces of his son-in-law for a joint campaign to seize the possessions of his rival Matei Basarab ended with the defeat of the Moldavian-Cossack army at Finta in Wallachia and the coming to power in Moldavia of Gheorghe Ștefan, who occupied Iasi and blocked the Suceava fortress, where Vasile Lupu’s wife closed herself. T. Khmelnytskyi again arrived at the head of the Cossack army to help the besieged in Moldova. His appearance near Suceava in August 1653 led to the ruin of this territory. Having made his way to the besieged and having organized a fortified camp with the Cossacks on the floor side of the fortress, the hetmanych found himself in a trap, being finally blocked upon the arrival in Suceava of the fresh forces of voivode Gheorghe Ștefan with contingents of Transylvanians, Wallachians and Poles. The Cossacks, besieged under the castle, were actively defending in the hope of helping the main forces of Hetman B. Khmelnytskyi, and also waiting for the Tatars recruited by Vasile Lupu. However, help did not arrive in time, and hunger, attacks, shelling and the death of T. Khmelnytskyi from a wound forced the Cossack garrison in early October to capitulate with honour to the allied forces, on the terms of free departure to Ukraine with the body of hetmanych. In general, the defence of Suceava in 1653 became the final episode of the Moldavian campaigns of Bohdan and Tymofii Khmelnytskyi (1650, 1653). After the death of his son and the surrender of Suceava, B. Khmelnytskyi lost interest in affairs in the Danube principalities and orientation towards Portа, placing further hopes in the fight against the Commonwealth on Moscow. The Hetman’s matchmaker, the former prince Vasile Lupu, having lost all hope of regaining the throne of Moldavia, ended up in a foreign land, being imprisoned in Istanbul, and the principality of Moldavia, which he involved in an alliance with the Cossacks, remained in the future a territory of military activity of neighbours, experiencing ruin.
ПАСТКА ДЛЯ ГЕТЬМАНИЧА: СУЧАВСЬКА КАМПАНІЯ Т. ХМЕЛЬНИЦЬКОГО (1653)
A TRAP FOR HETMANYCH: THE SUCEAVIAN CAMPAIGN OF T. KHMELNYTSKYI (1653)
Чернівецький національний університет ім. Юрія Федьковича
Keywords: Moldavia, Zaporizhzhia Army, Wallachia, Transylvania, Cossacks, Tatars, Porta, boyars, Vasile Lupu, Bohdan Khmelnytskyi, Tymofii Khmelnytskyi, Ruxandra Lupu, George II Rákóczi, Matei Basarab, Gheorghe Ștefan, Suceava.